2009
DOI: 10.1242/jeb.029058
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor trade-offs in mice selectively bred for high voluntary wheel running

Abstract: SUMMARYWe investigated sprint performance and running economy of a unique 'mini-muscle' phenotype that evolved in response to selection for high voluntary wheel running in laboratory mice (Mus domesticus). Mice from four replicate selected (S) lines run nearly three times as far per day as four control lines. The mini-muscle phenotype, resulting from an initially rare autosomal recessive allele, has been favoured by the selection protocol, becoming fixed in one of the two S lines in which it occurred. In homoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 63 publications
1
37
0
Order By: Relevance
“…24h) can be quantified as total revolutions, the amount of time activity and/or the average intensity of activity (e.g. Girard et al, 2007;Dlugosz et al, 2009;Gomes et al, 2009;Rezende et al, 2009). With video analysis, details of individual running bouts and the degree of intermittent locomotion can be quantified ) (see also Waters et al, 2008).…”
Section: Defining Voluntary Exercise and Spamentioning
confidence: 99%
“…24h) can be quantified as total revolutions, the amount of time activity and/or the average intensity of activity (e.g. Girard et al, 2007;Dlugosz et al, 2009;Gomes et al, 2009;Rezende et al, 2009). With video analysis, details of individual running bouts and the degree of intermittent locomotion can be quantified ) (see also Waters et al, 2008).…”
Section: Defining Voluntary Exercise and Spamentioning
confidence: 99%
“…However, any potential increase in escape ability may come at a cost. In particular, performance functions may trade-off with one another because of biomechanical, biochemical or physiological inter-relationships (Clobert et al, 2000;Vanhooydonck et al, 2001;Blake, 2004;Dlugosz et al, 2009). For example, previous studies on fish have indicated that the body morphology characteristics that are necessary to maximise the steady swimming efficiency are an increased depth of the anterior body and head, a shallow caudal region and a streamlined body shape (Fisher and Hogan, 2007), whereas unsteady swimming is maximised by a long, deep caudal region and a relatively shallow anterior body and head region (Webb, 1986;Law and Blake, 1996; Predator-driven intra-species variation in locomotion, metabolism and water velocity preference in pale chub (Zacco platypus) along a river Walker, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most tests of exercise V · O2,max have been performed on treadmills but some recent studies have utilized running wheel respirometry chambers (e.g. Chappell et al, 2004;Chappell and Dlugosz, 2009;Dlugosz et al, 2009;Dlugosz et al, 2012). Different methodologies can provide unequal V · O2,max values in treadmill tests (e.g.…”
Section: Introductionmentioning
confidence: 99%